Performance of Optical Receivers Using Photodetectors With Different Fields of View in a MIMO ACO-OFDM System - Cuiwei He; Wang, Thomas Q.; Armstrong, Jean (Journal of lightwave technology, 2015)
In this paper, we analyze the performance of optical receivers using photodetectors (PDs) with two different fields of view (FOVs) in a multiple-input multiple-output optical wireless communication system which uses intensity modulation and direct detection. The novel aspect is that the PDs in the receiver do not all have the same FOV. It is shown that the use of PDs with different FOVs leads to an invertible channel matrix even when the PDs are closely spaced. Simulations for a typical indoor visible light communications scenario where LED lights are used as data transmitters show that the signal-to-noise ratios at the equalizer outputs are much higher than for a receiver of the same dimension where all the PDs have the same FOV. Good performance can be achieved with PDs located in a 3.5 cm by 3.5 cm area. Finally, the overall bit error rate (BER) is calculated for systems using asymmetrically clipped optical OFDM as the modulation scheme. Results are presented for both zero forcing and minimum mean square error equalizers. It is shown that the BER varies with the receiver position, with higher values in the center and the corners of the room.